Determinasi penyaluran kredit umkm di provinsi kalimantan timur - Soeharjoto Soekapdjo (FORUM EKONOMI, 2019)
Purpose of this study is to know about determinants of small and medium scale enterprises (SME) credit distribution in East Kalimantan Province. Independent variable used third party saving, interest rate, and Consumer Price Index (CPI), while dependent variable is SME credit. Monthly data used from 2012-2017 with multiple linear regression methods. Result of this study is all independent variable significant to SME credit. Third party saving variable has positive influence to SME  credit, while interst rate and Consumer Pricing Index have negative influence to SME credit.